INDICATORS FOR ECONOMIC CORRIDOR DEVELOPMENT: AN APPROACH FROM INFRASTRUCTURE OPERATION AND SERVICES PERFORMANCE INDICATOR - Gunarta, IGW Samsi; Santosa, Wimpy; Sutandi, Anastasia Caroline (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The concept of economic corridor was introduced to be a breakthrough in the acceleration of economy development of the designated areas. The success of an economic corridor to grow further is determined by the performance of infrastructure, corridor services, and management of the corridor. The study aims at explaining the concept and process development of assessment tools to identify the service readiness and performances of Infrastructure to support development progress of corridors. A desk study has been conducted to identify parameters of measurements using public, government, and user views that might apply to Indonesian Economic Corridor. All parameters and indicators were selected on the basis of supply performances, quality of services, efficiency, utilization, and sustainability of the infrastructure. The study results in 9 outcomes and 31 infrastructure services indicators to be used in measuring corridor performance in relation infrastructure operations of the corridor. This only one side of the corridor performance assessment process but would be one of two important steps to able to assess the performance of Indonesian Economic Corridor grow beyond.